Low-Dose Radiation Advances in Coronary Computed Tomography Angiography in the Diagnosis of Coronary Artery Disease - Richards, Caryl E.; Obaid, Daniel R. (Current Cardiology Reviews, 2019)
Background: Coronary computed tomography angiography (CCTA) is now widely used in the diagnosis of coronary artery disease since it is a rapid, minimally invasive test with a diagnostic accuracy comparable to coronary angiography. However, to meet demands for increasing spatial and temporal resolution, higher x-ray radiation doses are required to circumvent the resulting increase in image noise. Exposure to high doses of ionizing radiation with CT imaging is a major health concern due to the potential risk of radiation-associated malignancy. Given its increasing use, a number of dose saving algorithms have been implemented to CCTA to minimize radiation exposure to “as low as reasonably achievable (ALARA)” without compromising diagnostic image quality. Objective: The purpose of this review is to outline the most recent advances and current status of dose saving techniques in CCTA. Method: PubMed, Medline, EMBASE and Scholar databases were searched to identify feasibility studies, clinical trials, and technology guidelines on the technical advances in CT scanner hardware and reconstruction software. Results: Sub-millisievert (mSv) radiation doses have been reported for CCTA due to a combination of strategies such as prospective electrocardiogram-gating, high-pitch helical acquisition, tube current modulation, tube voltage reduction, heart rate reduction, and the most recent novel adaptive iterative reconstruction algorithms. Conclusion: Advances in radiation dose reduction without loss of image quality justify the use of CCTA as a non-invasive alternative to coronary catheterization in the diagnosis of coronary artery disease.
Keywords: tube current modulation